2006
DOI: 10.1111/j.1600-0528.2006.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and severity of early childhood caries

Abstract: Infant bottle-feeding habits (either allowing a child to sip from a bottle during the day or put to sleep at night) and ethnicity other than Caucasian were significant determinants for both anterior caries pattern and severity of ECC in 4-5-year-old Australian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
111
1
18

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 41 publications
11
111
1
18
Order By: Relevance
“…Its etiology is complex and results from the interaction of several factors, such as: high consumption of fermentable carbohydrates, negligence in oral hygiene, low family socioeconomic status, and mother's limited educational level (20)(21)(22)(23) . This work showed that, when it comes to babies' oral hygiene, the education interventions of the above mentioned program were able to generate self-care skills in the mothers involved in the study and to stimulate healthy habits in their children (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Its etiology is complex and results from the interaction of several factors, such as: high consumption of fermentable carbohydrates, negligence in oral hygiene, low family socioeconomic status, and mother's limited educational level (20)(21)(22)(23) . This work showed that, when it comes to babies' oral hygiene, the education interventions of the above mentioned program were able to generate self-care skills in the mothers involved in the study and to stimulate healthy habits in their children (13) .…”
Section: Discussionmentioning
confidence: 99%
“…ECC was assessed according to the dmf-t World Health Organization (WHO) criteria 13 and categorised according to severity: 1,14 • dmf-t 0 = caries-free; • dmf-t 1-5 = low severity; or • dmf-t ≥ 6 = high severity.…”
Section: Children's Oral Examinationmentioning
confidence: 99%
“…La caries de infancia temprana presentó un impacto negativo con la CVRSB, similares hallazgos fueron encontrados en otros estudios (4,12,14,15,11,16). Abanto et al Observaron que el incremento en la severidad de caries dental en los niños presentó impacto negativo en la calidad de vida según la percepción de los padres, y esto es esperado debido al hecho que la enfermedad puede originar estas emociones, ya que la severidad de la caries usualmente produce una apariencia desagradable; el cual podría preocupar a los padres en relación a las oportunidades sobre la vida futura del niño (15).…”
Section: Discussionunclassified
“…En relación a las maloclusiones anteriores no se asociaron con un impacto negativo en la CVRSB de los niños y sus padres, esto es semejante con otros estudios (4,12,11,16 repentinamente, en las maloclusiones los cambios en la dentición se producen lentamente y en las etapas de desarrollo (4). Por lo tanto, las maloclusiones por lo general pasan desapercibidas en los niños y los padres y la mayoría de ellos no saben las consecuencias estéticas, psicológicas y económicas que pueden producir estas maloclusiones en edades más avanzadas(4).…”
Section: Discussionunclassified